Ultrafast dynamics in 2D materials investigated by time-resolved photoemission electron microscopy - Wang, Lin (2018)
This thesis includes my four-year researches on ultrafast dynamics on 2D materials using time-resolved photoemission electron microscopy (TR-PEEM). Our aim is to spatially investigate the dynamics on the atomic-layer thick materials. In Chapter 1, the background introduction of the ultrafast dynamics on 2D materials by different optical methods are discussed. While the applications of PEEM on surface science and the time resolved researches of the plasmonics of metal nanostructures are reviewed. At last, our motivation using TR-PEEM to investigate the ultrafast dynamics in semiconductor 2D materials is discussed. In Chapter 2, we briefly introduce our instrument firstly, then extract a 55-fs temporal resolution and an 80-nm spatial resolution through our delicate characterization of our instrument. we show that the apparatus can be used to investigate the sub-100-fs electronic relaxation dynamics. The time constant mapping result not only recovers the ensemble-averaged electronic relaxation time constant, but also directly yields the extent of spatial heterogeneity of the observed dynamics. In Chapter 3, we study the dynamics of WSe2 pumped by 2.41-eV light, find the spatial heterogeneity. The results help us to understand the influence of structural heterogeneities on the carrier dynamics of two-dimensional materials. In Chapter 4, the research on 4-layer MoS2 material by TR-PEEM reveals two Auger processes including Auger-mediated exciton formation and exciton-exciton annihilation process. In Chapter 5, we summary all the results discussed in Chapter 2 – 4, put forward some suggestions to further improve our experiments in future.